The fire - Russell, Bailey J. (Russell, Bailey J. Haunting of Hawthorne Harbor, 2021)
Aaron Hawthorne is relying on his nephew John to help him keep the Portal to the dead closed. But when John begins to act strangely and threatens him, Aaron suspects that someone is behind John's actions.